The Impact of Al-Biruni’s Astronomical Works on Modern Astronomy - Monjur-Ul-Haider, Mohammad; Rahman, Md. Mokhlesur (Advances in Social Sciences Research Journal, 2020)
Al-Biruni's foremosteffort on astronomy is mainly a blend of observational diagram and mathematical context. In his astronomical work, the Qanun-i Masoodi (al-Qanun al-Masudi, fi al-Hai'a wa al-Nujum), he uses his observational facts to challenge Ptolemy's steady solar 'apogee'.. Al-Biruni's eclipse facts was used by Dunthorne to supportcontrol the 'acceleration of the moon' and his observational facts has entered the more astronomical accounts and is still used today. The present paper aims to explore the major contributions of Al-Biruni to geophysics and astronomy as well as to identify the impacts of his works on the modern astronomy. Major findings indicate that Al-Biruni's key concern in astronomy was for calculations. He paid devotion to theoretical problems that had and have still been contributing to the development and critical analysis of both applied (in the procedure of solving problems), and theoretical (in the process of thought formulations) astronomy. This paper concludes that Al-Biruni's contributions must be seen in the comprehensiveness of his work, and in his continual attempts to formulate astronomical thoughts.